The impact of the financial crisis on the real economy - Bart van Ark; Michael Biggs; Thomas Mayer; Daniel Gros; Cinzia Alcidi (Intereconomics, 2010)
The cost of the financial crisis to the real economy has so far remained underexamined,probably because of the difficulty in making such an assessment. The crisis was precipitatedby an unsustainable bubble that artificially inflated economic fi ures, so what should be used as a benchmark for measuring the effects of the crisis on the real economy? How reliable are current estimates of the output gap? Could overestimating this indicator lead to underestimating the current risk of inflation? Finally, what effect will the crisis have on the declining long-term productivity gains in Europe and the USA, and what does this mean for potential output?
Keywords: 330